Wciornastki (Thysanoptera) lasów bukowych południowo-wschodniej Polski - Kucharczyk, Halina; Kucharczyk, Marek (Leśne Prace Badawcze, 2011)
During research carried out in beech forests at 12 sites in six regions of south-eastern Poland 84 species of Thysanoptera were collected. Six of the species were present in all six regions, and 36 species in only one of them. The richest fauna (59 spp.) was located in the vicinity of Iwonicz Zdrój (the Low Beskid Mts.), followed by that of the forests in the Sandomierz Basin (47 spp.); a similar number of species were present in the Roztocze region (30 spp.) and the vicinity of Lesko (the Sanocko-Turczańskie Mts. – 32 spp.). The smallest number of species were reported from beech forests of northern slopes of the Babia Góra massif (23) and the Ojców National Park (18). Altogether 27 arboricolous species were recorded, among them six were mycophagous. Using specific methods that connect the presence of thrips with particular favourable micro-environmental habitats, larvae and adult thrips were collected from their host plants. These methods made it easier to locate particularly rare and vulnerable species within the Polish fauna, such as: Thrips crassicornis Bagnall, Scolothrips uzeli (Schille) and Haplothrips crassicornis (John). We recognized that T. crassicornis Bagnall and T. fulvipes Bagnall are characteristic of beech forests, although the former is already known from south-eastern Poland. Numerical analyses UPGMA and PCA were used to explore the similarities among species composition of thrips assemblages occurring in the studied regions.